Long-term Results of Aortic Valve Replacement with the Starr-Edwards Valve. Issue 5637 (18th January 1969) - Fleming, James; Hamer, John; Hayward, Graham; Tubbs, O. S.; Hill, Ian
Abstract : Review of the 74 patients undergoing aortic valve replacement with a Starr–Edwards ball-valve prosthesis between October 1963 and December 1967 showed that 16 died during surgery or within the first month after operation, usually owing to myocardial failure; and there were nine late deaths. The remaining patients developed few major complications, and the long-term results of operation are considered satisfactory, no patient being grossly incapacitated and most of them are leading active, symptom-free lives.